A structured review of quantitative models in the blood supply chain: a taxonomic framework for decision making (2015)
This paper presents a structured review of the literature on quantitative modelling for the blood product supply chain. This is a widely-researched topic, dating back to the 1960s, and several other reviews have been published over the years. However, this paper presents new relevant information for researchers, not only by including more recent models but chiefly because of the structured way in which the models are presented. The models are broken down into five categories. The first four categories represent the four stages (echelons) in the supply chain: collection, production, inventory, and delivery. The final category contains “integrated” models which cover more than one stage. Each section (other than integrated models, which are treated slightly differently) contains two distinct elements. The first element is a diagrammatic representation of decisions and relationships, broken down by hierarchy level (strategic – tactical – operational). The second element is a text description of the main features, contributions and gaps found in the analysed models. An additional element for each section is available online, namely a searchable table describing specific features of each echelon, together with a taxonomic key to assist the reader.